Reactivation of Motor-Related Gamma Activity in Human NREM Sleep - Eichenlaub, Jean-Baptiste; Biswal, Siddharth; Peled, Noam; Rivilis, Nicole; Golby, Alexandra J.; Lee, Jong Woo; Westover, M. Brandon; Halgren, Eric; Cash, Sydney S. (Frontiers in Neuroscience, 2020)
Models of memory consolidation posit a central role for reactivation of brain activity patterns during sleep, especially in non-Rapid Eye Movement (NREM) sleep. While such “replay” of recent waking experiences has been well-demonstrated in rodents, electrophysiological evidence of reactivation in human sleep is still largely lacking. In this intracranial study in patients with epilepsy (N=9) we explored the spontaneous electroencephalographic reactivation during sleep of spatial patterns of brain activity evoked by motor learning. We first extracted the gamma-band (60-140Hz) patterns underlying finger movements during a tapping task and underlying no-movement during a short rest period just prior to the task, and trained a binary classifier to discriminate between motor movements vs. rest. We then used the trained model on NREM sleep data immediately after the task and on NREM sleep during a control sleep period preceding the task. Compared with the control sleep period, we found, at the subject level, an increase in the detection rate of motor-related patterns during sleep following the task, but without association with performance changes. These data provide electrophysiological support for the reoccurrence in NREM sleep of the neural activity related to previous waking experience, i.e., that a basic tenet of the reactivation theory does occur in human sleep.